Aplikasi Mikrokontroler Arduino Pada Sistem Irigasi Tetes Untuk Tanaman Sawi (Brassica Juncea) (Application of Arduino Microcontroller on Drip Irrigation for Mustard Plant (Brassica juncea): Application of Arduino Microcontroller on Drip Irrigation System for Mustard Plant (Brassica juncea) - M. Salman Ibnu Chaer; Sirajuddin H. Abdullah; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Arduino Uno microcontroller (ATmega328) is an automatic control device which function to control, capture and store data that can be used to design electronic circuits to control on/off irrigation. In order to determine its performance, application of on/off irrigation control circuit in agriculture field need to be conducted. Mustard plant were selected for this experiment due to its sensitivity on irrigation. Purpose of this study was to applied control system based drip irrigation using Arduino microcontroller on mustard plant cultivation to compare growth and productivity of mustard plant using automatic irrigation based microcontroller and using manual irrigation, which adjusted to plants water requirement. Method used in this research was experimental method by trial on the field. Observed parameter consist of changes in moisture content, performance of on/off irrigation control system, quantity of irrigation water, plant height, number of leaves, length and width of the leaves, plants weight and crop productivity. Setting point for lower limit soil moisture content was 25.47% and the upper limit was 28.73%. During the experiment, three times watering were conducted, i.e. at 11, 16 and 20 days after planting, with total quantity of water 5,200 ml. Height of mustard plants using automatic irrigation was 21.26 cm and using manual irrigation was 22.6 cm; number of mustard plant leaf using automatic irrigation was 13 leaves and using manual irrigation was 13.4 leaves; length and width of mustard plant leaf using automatic irrigation was 17.07 cm and 8.05 cm, while using manual irrigation was 20.75 cm and 9.73 cm; mustard plant productivity using automatic irrigation was 13.54 ton/ha and using manual irrigation was 17.41 ton/ ha.